Financial Feasibility Study And Economic Impact Of Krl Electrification Project Development Yogyakarta - Solo - Sapto Priyanto; Erifendi Churniawan; Endras Setyo Darmawan (Jurnal Syntax Transformation, 2023)
At the beginning of 2022, the Ministry of Transportation through the Directorate General of Railways made improvements in railway operations by developing electrification of the Yogyakarta – Solo KRL line to Palur Station to support the progress of the railway. The development of electrification is one form of development across Yogyakarta – Solo as a real step by the government to provide effective and efficient mass transportation services to support the mobilization of the people of Solo as part of the golden triangle in Central Java This research was conducted to determine the financial feasibility that is the basis for carrying out all activities in life as well as the economic impact generated by the extension of the Yogyakarta-Solo KRL line to Palur Station. In this study, researchers will calculate several aspects, namely net present value (NPV), internal rate of return (IRR), benefit cost ratio (B/C ratio), fuel cost savings and time value savings The method used in this study is the study of literature. This research is expected to provide input to operators and regulators regarding financial independence and the economic impact of the implementation of the Yogyakarta - Solo KRL